Opportunities for Innovation in Genetic Transformation of Forest Trees - Nagle, Michael; Déjardin, Annabelle; Pilate, Gilles; Strauss, Steven H. (Frontiers in Plant Science, 2018)
The incorporation of DNA into plant genomes followed by regeneration of non-chimeric stable plants (transformation) remains a major challenge for most plant species. Forest trees are particularly difficult as a result of their biochemistry, ageing, desire for clonal fidelity, delayed reproduction, and high diversity. We review two complementary approaches to transformation that appear to hold promise for forest trees. Developmental genes (DG) may be useful tools for promoting transformation. DGs, which can act through a wide variety of developmental mechanisms to promote regeneration of transgenic cells, have been widely employed in model plants to promote embryogenesis and in some cases organogenesis. Following initial experimental demonstration in dicots, the DGs WUSCHEL and/or BABY BOOM have formed the basis of a high efficiency method for a variety of monocot genotypes and species. However, in dicots the utility of these genes as the basis of a robust transformation system has not been demonstrated. Many additional DGs appear capable of promoting regeneration that have not been systematically explored as transformation tools. Because in vitro plant transformation systems are costly and must be customized for each new genotype and species, in vivo approaches to transformation hold much appeal. It is possible to produce stable transgenic plants by agro-inoculation of seeds or vegetative/floral buds, but as yet these approaches have not been used routinely in any plant species except for the Arabidopsis floral dip. We will discuss how the Arabidopsis system, and other in planta techniques, may be tailored for forest trees, taking into account variations in biology of different taxa.